ANTIMICROBIAL RESISTANCE OF BACTERIA ISOLATED FROM NASOPHARYNGEAL SPECIMENS IN CHILDREN UNDER FIVE WITH ACUTE PNEUMONIA AT THAI NGUYEN NATIONAL HOSPITAL, 2023–2024 (Vietnam Journal of Community Medicine, 2026)
Background: Pneumonia remains a major cause of morbidity in children under five years of age. The increasing prevalence of antimicrobial resistance poses a significant challenge in the management of pediatric pneumonia. Surveillance of bacterial pathogens and their resistance patterns is essential to guide appropriate empirical antibiotic therapy.Objectives: To describe bacterial distribution and antibiotic resistance patterns among isolates from nasopharyngeal samples of children under five with acute pneumonia at Thai Nguyen National Hospital , 2023–2024.Methods: A retrospective descriptive study was conducted on bacterial isolates obtained from nasopharyngeal specimens of children under five years of age diagnosed with acute pneumonia and treated at Thai Nguyen National Hospitalfrom January 2023 to December 2024. Data on bacterial culture, identification, and antimicrobial susceptibility testing were extracted from the Labconn system. Antimicrobial susceptibility results were interpreted according to CLSI 2023/EUCAST 2023 guidelines.Results: Among 4,548 nasopharyngeal specimens, the bacterial culture positivity rate was 22.71%. Positive cultures were predominantly observed in children under three years of age. Streptococcus pneumoniae was the most frequently isolated pathogen (67.28%), followed by Staphylococcus aureus (19.07%). S. pneumoniae exhibited high resistance rates to penicillin, erythromycin, tetracycline, and trimethoprim/sulfamethoxazole, while remaining highly susceptible to fluoroquinolones, vancomycin, and linezolid. A high proportion of oxacillin-resistant S. aureus was identified, indicating a substantial prevalence of methicillin-resistant Staphylococcus aureus (MRSA).Conclusions: Bacterial isolates from nasopharyngeal specimens of children under five years of age with acute pneumonia at Thai Nguyen National Hospital showed high levels of antimicrobial resistance, particularly among Streptococcus pneumoniae and Staphylococcus aureus, providing valuable data for local antimicrobial resistance surveillance and rational antibiotic use.
Keywords: Pneumonia, antibiotic, antibiotic resistance.